Thermo-fluid characterization of flue gas flows through a packed bed - Vorayos N. (2014)
Enhancement of thermal performance in an incinerator and flue gas treatment with a randomly packed bed of uniform spheres was investigated in a custom-made experimental facility and reported in the present paper. Pressure drop, temperature evolution and heat transfer characteristics were evaluated for a range of superficial velocities, Reynolds numbers and bed geometries. Results revealed that increases in both superficial velocity and bed thickness caused a rise in pressure drop across the packed bed in similar fashion to the Ergun equation but with different coefficients at low Reynolds number between 60-300. The two constants were empirically determined to be 68.5 and 4.95. It was also found that the packed bed affects axial temperature distribution from the incinerator chamber to stack. For the same heating rate, higher temperature was achieved in the chamber with the packed bed, and peak temperature was reached at a rate of 7-10% faster than that without the packed bed during the startup period. The downstream side of the thicker bed appeared to have lower temperature than the thinner bed for the same axial position, demonstrating less flue loss during the transient state. The incinerator chamber proved to have higher temperature rising rate and reached higher maximum temperature with the presence of the packed bed. © 2008 The Korean Society of Mechanical Engineers and Springer-Verlag GmbH.